Clinical and sociodemographic correlates of suicidality in patients with major depressive disorder from six Asian countries - Lim, A.Y.; Lee, A.R.; Hatim, A.; Tian-Mei, S.; Liu, C.Y.; Jeon, H.J.; Udomratn, P.; Bautista, D.; Chan, E.; Liu, S.I.; Chua, H.C.; Hong, J.P.; et al. (BMC, 2014)
Background: East Asian countries have high suicide rates. However, little is known about clinical and sociodemographic factors associated with suicidality in Asian populations. The aim of this study was to evaluate the factors associated with suicidality in patients with major depressive disorder (MDD) from six Asian countries. Methods: The study cohort consisted of 547 outpatients with MDD. Patients presented to study sites in China (n = 114), South Korea (n = 101), Malaysia (n = 90), Singapore (n = 40), Thailand (n = 103), and Taiwan (n = 99). All patients completed the Mini-International Neuropsychiatric Interview (MINI), the Montgomery-Asberg Depression Rating Scale (MADRS), the Global Severity Index(SCL-90R), the Fatigue Severity Scale, the 36-item short-form health survey, the Sheehan Disability Scale, and the Multidimensional Scale of Perceived Social Support (MSPSS). Patients were classified as showing high suicidality if they scored >= 6 on the MINI suicidality module. Multivariate logistic regression analysis was used to examine sociodemographic and clinical factors related to high suicidality. Results: One hundred and twenty-five patients were classed as high suicidality. Unemployed status (adjusted odds ratio OR 2.43, p < 0.01), MADRS score (adjusted OR 1.08), p < 0.001, and GSI (SCL-90R) score (adjusted OR 1.06, p < 0.01) were positively related to high suicidality. Hindu (adjusted OR 0.09, p < 0.05) or Muslim (adjusted OR 0.21, p < 0.001) religion and MSPSS score (adjusted OR 0.82, p < 0.05) were protective against high suicidality. Conclusions: A variety of sociodemographic and clinical factors were associated with high suicidality in Asian patients with MDD. These factors may facilitate the identification of MDD patients at risk of suicide.